Carbonatecalcium equilibrium ion content in drinking groundwater of the Kyiv region - Kalinin, І.V.; Bogatyrenko, V.A.; Bilenko, M.A.; Nesterovskyi, V.A.; Yevdokymenko, V.A. (Reports of the National Academy of Sciences of Ukraine, 2020)
Currently, the quality of water resources is becoming a factor that limits and regulates water use processes, and, most of all, it relates to drinking water. Increasing frequency of deviations of the drinking water quality of water supply systems of Ukraine from the regulatory requirements is the main reason for the use of underground drinking water of non-centralized water supply for the population of Ukraine. Groundwater is usually more protected from the effects of industrial and economic activities. The groundwater of the Kyiv region is represented by the aquifer complex of the western part of the Dnieper-Donets artesian basin (DAB): the Quaternary tier (at depths of 30—50 m), Kharkiv horizon (≈ 90 m), Buchach horizon (within 60—120 m depth), aquifer the Cenomanian-Callovian horizons (120—160 m) and Middle Jurassic deposits. According to the hydrogeological model, this artesian system is characterized by the intense vertical water exchange of mainly downward filtration of gravitational groundwater due to the high fracture and permeability of separate weakly permeable layers. Through pores and cracks, a considerable mass transfer of dissolved chemicals occurs, which causes the variable cationic and anionic compositions of groundwater, as well as concentration fluctuations of pore solutions. The surface water, whose quality is highly dependent on both climatic conditions and human activity, gradually penetrate through a system of pores and cracks into the artesian basins of the DAB, creating the prerequisites for their contamination. Accordingly, the monitoring of the state of groundwater within the Kyiv region is necessary and should be permanent. The results of experimental data on the groundwater quality, namely pH, total acidity, alkalinity, and content of calcium and magnesium ions are obtained in the period April—October 2017. On their basis, the parameters of the ionic molecular composition of the carbonate-calcium equilibrium system were calculated, as well as the aggressiveness and stability of groundwater depending on the season — spring, summer, and autumn. It is shown that the changes of the carbonate-calcium equilibrium in the groundwater system of the Kyiv region are closely interconnected with the atmospheric precipitation and depend on the periods of seasonal fluctuations of precipitation (maximum falls in April and October 2017), according to the State Geological Information Fund of Ukraine on climate seasonal changes in 2017. In all aquifers during the periods of intense rainfall and low temperatures, the content of free CO2 increases, which is mainly included in the carbonate-calcium equilibrium system. Fluctuations in the carbon dioxide content also correspond to seasonal changes in pH: the more CO2 is dissolved in water, the lower the pH. In the dry season, the maximum content of ions in the water is observed, which, in turn, coincides with the maximum value of the degree of saturation of SICaCO3. Groundwater has a sufficiently high degree of saturation of CaCO3, the metastable nature of which is explained by the low concentrations of anions and the predominant amount of HCO3 ions, provided that the pH fluctuates within pH = 6 ÷ 8. Upon reaching the surface, such carbonates (sediments) are easily formed in such waters. Therefore, before use, groundwater within the Kyiv region, the additional purification is needed to reduce the carbonate hardness of water. According to the Langelier index, they are not corrosive.